2018
DOI: 10.1037/bne0000267
|View full text |Cite
|
Sign up to set email alerts
|

When is the rat retrosplenial cortex required for stimulus integration?

Abstract: The rodent retrosplenial cortex is known to be vital for spatial cognition, but evidence has also pointed to a role in processing nonspatial information. It has been suggested that the retrosplenial cortex may serve as a site of integration of incoming sensory information. To examine this proposal, the current set of experiments assessed the impact of excitotoxic lesions in the retrosplenial cortex on two behavioral tasks that tax animals’ ability to process multiple and overlapping environmental stimuli. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In some cases, these cues are related to navigation, but in other cases they are not necessarily spatial in nature, providing evidence that RSC is also involved in learning and memory beyond spatial processing. Consistent with the burgeoning interest of how the RSC may be involved in nonspatial forms of learning and memory, Nelson, Hindley, Vann, and Aggleton (2018) present findings regarding potential contributions of the RSC to stimulus integration, reporting data that are consistent with a role for the RSC when the meaning of a stimulus changes during task performance. However, in a related article, Nelson, Powell, Kinnavane, and Aggleton (2018) report that lesions of a related structure, the anterior thalamus, but not the RSC, impact latent inhibition.…”
supporting
confidence: 84%
“…In some cases, these cues are related to navigation, but in other cases they are not necessarily spatial in nature, providing evidence that RSC is also involved in learning and memory beyond spatial processing. Consistent with the burgeoning interest of how the RSC may be involved in nonspatial forms of learning and memory, Nelson, Hindley, Vann, and Aggleton (2018) present findings regarding potential contributions of the RSC to stimulus integration, reporting data that are consistent with a role for the RSC when the meaning of a stimulus changes during task performance. However, in a related article, Nelson, Powell, Kinnavane, and Aggleton (2018) report that lesions of a related structure, the anterior thalamus, but not the RSC, impact latent inhibition.…”
supporting
confidence: 84%
“…In addition, besides RSC [ 10 ], HD-specific signals were also found in human medial parietal cortex [ 16 ], prestriate cortex [ 17 ], and deep layers of V1 [ 18 ] in rats. RSC has been implicated in sensory integration [ 63 ]. However, the classical subdivision of RSC into dysgranular and granular regions also hides a more fine-grained anatomical parcellation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with prior studies that used multimodal stimuli (Robinson et al, 2011(Robinson et al, , 2014, these findings suggest that RSC is essential for linking together cues prior to any reinforcement. It is possible that the RSC's role in S-S associations (in the absence of reinforcement) may be selective; recent studies have demonstrated that the RSC does not necessarily contribute to learning and memory in other conditioning paradigms involving multiple cues (see Nelson, Hindley, Vann, & Aggleton, 2018;Todd, Fournier, & Bucci, 2019). Nevertheless, the results of this and other sensory preconditioning experiments have suggested a role for the RSC in the formation of S-S associations in the absence of reinforcement, consistent with the framework provided by Bucci and Robinson (2014).…”
Section: Discussionmentioning
confidence: 99%